2023
DOI: 10.1002/wcc.861
|View full text |Cite
|
Sign up to set email alerts
|

A review of ENSO teleconnections at present and under future global warming

Omid Alizadeh

Abstract: The El Niño‐Southern Oscillation (ENSO) is a major component of the Earth's climate that largely influences global climate variability through long‐distance teleconnections. Rossby wave trains emerging from the tropical convection and their propagation into extratropical regions are the key mechanism for tropical and extratropical teleconnections. Despite significant progress in the understanding of ENSO teleconnections over the recent past decades, several important issues have remained to be addressed. The g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 150 publications
0
1
1
Order By: Relevance
“…Yu and Kim (2011) studied the relationship between different phases of ENSO and SLP in extratropical regions and concluded that the warm phase of ENSO (El Niño) strengthens the Aleutian low pressure, and the cold phase has the opposite effect. According to the positive trends of the warm phases of ENSO (Yu and Kim 2011;Alizadeh, 2023), the strengthening of the Aleutian low pressure is expected, but with the results of this study and the weakening trend of this low pressure, it can be concluded that the impact of global warming on this low pressure is undeniable. However, further discussion and examination can be conducted in future studies.…”
Section: The Pacific Ocean and Aleutian Lowcontrasting
confidence: 49%
“…Yu and Kim (2011) studied the relationship between different phases of ENSO and SLP in extratropical regions and concluded that the warm phase of ENSO (El Niño) strengthens the Aleutian low pressure, and the cold phase has the opposite effect. According to the positive trends of the warm phases of ENSO (Yu and Kim 2011;Alizadeh, 2023), the strengthening of the Aleutian low pressure is expected, but with the results of this study and the weakening trend of this low pressure, it can be concluded that the impact of global warming on this low pressure is undeniable. However, further discussion and examination can be conducted in future studies.…”
Section: The Pacific Ocean and Aleutian Lowcontrasting
confidence: 49%
“…; (v) How could change synchronization patterns on ENSO under climate change? Recent literature suggests that ENSO teleconnections could vary substantially under the influence of global warming (Alizadeh, 2024) and (vi) How are the patterns of synchronization between the Amazon convection and precipitation in the tropical Andes? Segura et al (2019) found relationships between those processes but a synchronization approach is an open topic.…”
Section: Final Remarks and Future Workmentioning
confidence: 99%